(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-3-46-54 This study explores the use of manipulative techniques in print advertising. The attention is paid to the distribution of communicative roles, the use of expressive means, choice of targets of influence and ways to compete against rivals. This analysis shows the evolution of advertising for health products. Key words: manipulation, health products, print media, Spanish